Attitudes and beliefs about exercise among elderly African Americans in an urban community. - Lavizzo-Mourey, R. (National Medical Association, 2001)
Older African Americans are less likely to exercise compared with their white counterparts. Few studies have examined the facilitating factors and barriers to exercise among older African Americans living in urban communities. This study represented the first phase of a program to develop an exercise intervention in an urban community. Qualitative research was conducted to identify culturally determined attitudes that could be useful in designing an effective exercise program. Five focus groups involving 38 persons from a variety of settings were facilitated by trained professionals. Transcripts were analyzed to identify themes and contrasts among group participants. Contrary to the expectations of the investigative team, focus-group participants: (1) uniformly preferred group exercises compared with exercising at home, (2) rejected walking as a feasible option because of safety concerns, and (3) expressed limited interest in using weights or Eastern exercises such as Tai Chi. Concepts and goals of exercise differed according to the physical capabilities of the participants. The analysis of these focus-group discussions provided valuable insights with regard to the development of our community-based exercise-intervention protocol. These findings may be important in designing effective exercise programs for older African Americans in urban settings.